Pengaruh Substitusi Tepung Ampas Kelapa (Cocos Nucifera)pada Pembuatan Kue Klemben terhadap Daya Terima Konsumen - Fatimah Ayu Widiasari; Mahdiyah Mahdiyah; Maariani Maariani (Jurnal Syntax Transformation, 2022)
This study aims to determine the effect of substitution of coconut dregs flour for wheat flour in making klemben cakes on consumer acceptance. The method used in this study is an experimental method using organoleptic tests. This research was started by making coconut dregs flour, then substituted into the cake batter as much as 10% (P1), 20% (P2) and 30% (P3). Based on the results of the organoleptic test of the klemben cake product with 10%, 20% and 30% coconut dregs flour substitution, it was well received by consumers. This is shown from the results of the product assessment covering 5 aspects with the results of the like and really like categories. Based on the results of testing the hypothesis using the Friedman test, it showed that the treatment had no effect on the inner color, outer color, coconut taste, sweet and savory taste, aroma, texture and voids, so it was not continued to the Tuckey test in general, the results of coconut dregs flour substitution in Klemben cakes were acceptable. and liked by consumers on a scale of like to like very much. The conclusion of this entire study shows that the percentage of coconut dregs flour substitution of 10%, 20%, and 30% are all liked by consumers, this can be seen from the average score of inner color, outer color, coconut taste, sweetness, aroma, Crisp texture and cavity appearance are above 4.